Deriving Recruitment and Spawning Patterns from a Survey of Juvenile Grouper (Pisces: Serranidae) Occurrences in the Philippines - Mamauag, Samuel; Penolio, Lutgarda; Aliño, Porfirio (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 1 (2001), 2007)
Preliminary data on the patterns of occurrence of juvenile groupers in the Philippines was examined. Survey questionnaires were randomly distributed to respondents (i.e., fishers and traders of juvenile groupers). Patterns of presence/absence of the juveniles were examined and recruitment and spawning patterns were inferred from survey results. Results showed that patterns of recruitment of juvenile groupers in the Philippines varied greatly with each area/region. The large variability in the recruitment patterns precluded a "general pattern". Upon closer examination, however, some emergent signals were noted, albeit not very strong. Spatio-temporal patterns for recruitment of juvenile groupers seemed to be influenced by change in seasons (summer and wet) and monsoons (northeasterlies and southwesterlies). Inferred spawning patterns likewise varied with area/region and an inter-specific variation in spawning behaviour may be possible. Although results are preliminary due to lack of intensive data verification, a more rigorous type of sampling protocol is worth pursuing in the future. The results of this preliminary examination provided insights on the recruitment of the commercially important epinepheline serranids in the Philippines.
Keywords: groupers; lapu-lapu; fish recruitment; spawning patterns